2006
DOI: 10.1007/s00595-006-3273-y
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Valve Myxoma Mimicking Vegetation: Report of a Case

Abstract: We report a case of cardiac myxoma of the aortic valve. To our knowledge, this represents only the seventh such case ever documented. A 61-year-old woman underwent an echocardiography to screen for hypertensive-diabetic cardiac complications, which showed a mass on her aortic valve. Although she had not experienced a fever, the mass closely resembled a vegetation, resulting in an initial diagnosis of infective endocarditis. We extirpated the mass and repaired the aortic valve with the patient under cardiopulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 4 publications
1
21
1
Order By: Relevance
“…To the best of the authors' knowledge, only 11 cases of aortic valve myxoma have been previously reported in the literature [ Table 1]. [4][5][6][7][8][9][10][11][12][13][14] Interestingly, nine of these previously reported patients were male, as in the current case; this is contrary to the usual female preponderance of myxoma cases. 1,[4][5][6][7][8][9]11,13,14 Overall, six aortic valve myxoma patients were symptomatic, with symptoms largely attributable to distal embolisation and ischaemia, including three cases with stroke, two with myocardial infarctions and one with limb ischaemia.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…To the best of the authors' knowledge, only 11 cases of aortic valve myxoma have been previously reported in the literature [ Table 1]. [4][5][6][7][8][9][10][11][12][13][14] Interestingly, nine of these previously reported patients were male, as in the current case; this is contrary to the usual female preponderance of myxoma cases. 1,[4][5][6][7][8][9]11,13,14 Overall, six aortic valve myxoma patients were symptomatic, with symptoms largely attributable to distal embolisation and ischaemia, including three cases with stroke, two with myocardial infarctions and one with limb ischaemia.…”
Section: Discussioncontrasting
confidence: 60%
“…[4][5][6][7][8][9][10][11][12][13][14] Typically, the management of aortic valve myxoma cases involves the surgical excision of the tumour as well as the surrounding tissue to minimise the risk of local recurrence, as in the present case. 4,[10][11][12] During the procedure, the native aortic valve should be conserved as much as possible; however, if the tumour is too large The differential diagnosis of an aortic valve myxoma includes vegetation, a thrombus, PFE and Lambl's excrescences; these conditions can be distinguished by their microscopic and immunohistochemical characteristics. 7,10,13 In addition, thrombi and myxomas can be differentiated using two-dimensional echocardiography; the former typically present with a layered appearance, while an area of echolucency may be observed within the tumour in the latter.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On clinical examination, one of the patients presented with embolic myocardial infarction,4 three patients had embolic stroke,6–8 one had embolic occlusion of the abdominal aorta, one patient demonstrated embolic occlusion of the common femoral artery9 and three patients exhibited an incidental finding on TTE 5 10 11. Furthermore, the myxoma was attached to the right coronary cusp in three patients,6 7 11 to the left coronary cusp in two patients (including the present case),10 and to the non-coronary cusp in two patients4 5; two patients exhibited fusion of the left and right coronary cusps 8 9. Valvular myxomas tend to have a smaller cellular component, fewer giant cells and less perivascular cuffing of tumour cells 12…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of surgical resection with clear margins, while preserving the valve architecture4 10 and valve repair or replacement,9–11 is dependent on the size of the tumour, in order to prevent recurrence. In cases without complex myxoma syndrome, recurrence of tumour is rare if the resection is appropriately performed 13.…”
Section: Discussionmentioning
confidence: 99%